2017
DOI: 10.1371/journal.pgen.1006739
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the impact of Lynch syndrome-causing missense mutations from structural calculations

Abstract: Accurate methods to assess the pathogenicity of mutations are needed to fully leverage the possibilities of genome sequencing in diagnosis. Current data-driven and bioinformatics approaches are, however, limited by the large number of new variations found in each newly sequenced genome, and often do not provide direct mechanistic insight. Here we demonstrate, for the first time, that saturation mutagenesis, biophysical modeling and co-variation analysis, performed in silico, can predict the abundance, metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
147
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 100 publications
(162 citation statements)
references
References 53 publications
15
147
0
Order By: Relevance
“…The maximal difference in intensity was approximately five‐fold, and when plotting the normalized values against the predicted thermodynamic stability of the selected variants, we observed that those PAH variants with high ΔΔG values also generally displayed a reduced steady‐state level (Figure B). Fitting this to a thermodynamic model of protein degradation (Nielsen et al., ) indicates an effective in vivo stability of −2.8 ± 0.2 kcal/mol for the wild‐type PAH monomer. Conceptually, this value indicates the average amount of stability loss that the protein can tolerate before protein levels drop to 50%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The maximal difference in intensity was approximately five‐fold, and when plotting the normalized values against the predicted thermodynamic stability of the selected variants, we observed that those PAH variants with high ΔΔG values also generally displayed a reduced steady‐state level (Figure B). Fitting this to a thermodynamic model of protein degradation (Nielsen et al., ) indicates an effective in vivo stability of −2.8 ± 0.2 kcal/mol for the wild‐type PAH monomer. Conceptually, this value indicates the average amount of stability loss that the protein can tolerate before protein levels drop to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Sepiapterin (Santa Cruz Biotechnology) was used at a concentration of 100 μM. Degradation was followed in cultures treated with cycloheximide (Sigma) as described previously (Nielsen et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations